Lscuo ceramics as possible material for thermoelectric energy conversion (2009)
Oxide ceramics of La1.85Sr0.15CuO4-d (LSCuO) were grown by using the solid-state reaction method. The oxygen stoichiometry was modified by submitting the obtained samples to a post-growth thermal process at 9000C under an inert atmosphere. Powder X-ray diffraction analysis shows all samples are single-phase with K2NiF4-type structure. The thermoelectric properties were studied from Seebeck coeficient S(T) and electrical resistivity ρ(T) measurements in the temperature range from 90 to 290K. The magnitude of S(T) and ρ (T) increases with the processing time reaching maximum values, at room temperature, close 150μV/K and 0:8m Ω - cm, respectively. From S(T) and ρ (T) data it was possible to calculate the thermoelectric power factor PF, which reaches maximum values close to 38μW/K2cm in the temperature range between 90 and 160K. The behavior of the transport properties and PF becomes these ceramics promissory thermoelectric materials, which could be used in low temperature thermoelectric applications.